Improving Student Understanding on Theme 1 of Human and Environmental Subthemes Through Talking Stick Method Class V-B MI Wachid Hasjim Sidoarjo - Khusnah, Miftakhul (Indonesian Journal of Science Learning (IJSL), 2020)
This research is motivated by the low level of understanding of VB grade students on Theme 1 of the Human Subtheme and the material environment about human motion organs. One reason is that learning on this theme, teachers use less varied methods. The number of students whose grades reached KKM 75 on the thematic material is only 25% of the total number of students. The alternative method chosen to overcome this problem is to use the talking stick method. The purpose of this study are: 1) to find out the application of the talking stick method to improve students' understanding of Theme 1 of the Human Subtheme and the classroom environment of MI Wachid Hasjim Sidoarjo. 2) Find out the increase in students' understanding of Theme 1 Subtheme of humans and the environment after the application of the talking stick method in VB MI Wachid Hasjim Sidoarjo class. The research method used in this study is the classroom action research (CAR) method using the Kurt Lewin model. Data collection techniques used in this study were interviews, observation, documentation, and tests. The results showed that: 1) the application of the talking stick method can be implemented well as evidenced by the results of the observation of teacher activity increased from a value of 79.3 (enough) in the first cycle increased to 91.4 (very good) in the second cycle. The results of observation of student activities get a final value of 78.8 (enough) in the first cycle increased to 94 (very good) in the second cycle. 2) The increase in students' understanding after applying the talking stick method increased from 25% of students who completed the pre-cycle, in the first cycle increased to 57.5% (enough) and in the second cycle increased to 80% (good).